FFT241 : Theatre production / College of Creative Arts - UiTM, College of Creative Arts
This course provides the students with the knowledge and skills demanded to work in the professional theatre industry. The students will be exposed to perform on stage, involve at the backstage, design and build the set, props, costumes, lighting and also work as the management team in the production. Through this course it will develop the hands on expertise. The collaborative artistic environment important in training the students to become the processional and hold on a strong discipline in the field. This course will require the students to produce a substantial body of original theatrical work, from acting or directing or design for the theatre (scenography – set, lighting, costume, sound/audio design) by showing a wide range of creative, technical, organizational and presentational skills and understanding. The content will be developed from the collaboration between student and the course supervisors in producing a theatre work. At the end of the course, the students able to produce a theatre production that involves every department in creating a full production from the performers until the production team. This will be a very challenging course that demand focus and dedication from the students.